2021
DOI: 10.3390/molecules26092458
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biological Activity of a Novel Preparation of Lavandula angustifolia Essential Oil

Abstract: Lavandula angustifolia, one of the most popular medicinal plants, is the source of a bioactive essential oil characterized by a wide spectrum of biological activity, e.g., antiseptic, analgesic, and anticancer effects. In dermatology, the oil helps to relieve skin inflammation and exhibit wound healing potential. However, the mechanism of action of the lavender oil depends on its composition, which in turn is dependent on the origin and growing conditions. Our study aimed to compare the composition and prorege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The cited standards confirmed that low levels of camphor and eucalyptol are important in lavender essential oil to differentiate it from lavandin oil. Previous works showed a broad spectrum of the biological activities of this EO, which is used for its sedative, anti-inflammatory, antioxidant, antimicrobial, and antifungal properties, in addition to its use as an insecticide and larvicides, and as an anticancer remedy and food additive [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cited standards confirmed that low levels of camphor and eucalyptol are important in lavender essential oil to differentiate it from lavandin oil. Previous works showed a broad spectrum of the biological activities of this EO, which is used for its sedative, anti-inflammatory, antioxidant, antimicrobial, and antifungal properties, in addition to its use as an insecticide and larvicides, and as an anticancer remedy and food additive [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity (IC50) of lavender oil was reported to be 0.28 µg/mL on HEL 12469 human embryo lung cells by Puškárová et al [5]. In another study, Miastkowska et al compared commercial and harvested Lavender essential oils and reported 0.20 v/v and 0.36 v/v for the HaCaT cell line, respectively [15]. In addition, Cardia et al reported that lavender essential oil showed low cytotoxicity on mice leukocytes obtained from the peritoneal cavity, with cell viability greater than 75% up to a concentration of 10 µg/mL [16].…”
Section: Discussionmentioning
confidence: 99%
“…Kozics et al [ 71 ] determined a value of IC50 of 0.043% on the human cell line HaCaT (normal keratinocytes). The HaCaT line was used by Miastkowska et al [ 72 ] too, observing that in the case of commercial L. angustifolia EO the value of IC50 was lower (0.20%) than that of the in-house one (0.36%). In another study conducted by Niksic et al [ 73 ], a significant antiproliferative activity of L. angustifolia EO on three cancer cell lines, MOLT-4 (acute lymphoblastic leukemia), MCF-7 (mammary adenocarcinoma) and NCI-H460 (pulmonary carcinoma), was reported.…”
Section: Discussionmentioning
confidence: 99%